Pig feed capable of preventing sow erythroderma and preparation method of pig feed - BAI HUIJUAN (2016)
The invention discloses pig feed capable of preventing sow erythroderma and a preparation method of the pig feed. The feed is prepared from the following components: corns, rice bran, table salt, purple sweet potatoes, sweet potato leaves, protein powder, Chinese yams, high-stem cabbages, peanut leaves, honeysuckle flowers, wrinkled gianthyssop herb, hawthorn fruits, liquorice roots, wild chrysanthemum flowers, fructus forsythiae, radix bupleuri, fructus arctii, tangerine peels and a compound additive. The feed disclosed by the invention is reasonable and scientific in component; and nutrients of sows are met and the self immunity can also be enhanced; and the sow erythroderma can be prevented as soon as possible. A preparation process of the pig feed is simple and efficient and is suitable for popularizing in a large scale. 本发明公开了种预防母猪红皮病的猪饲料及其制备工艺，该饲料由以下组分构成：玉米、米糠、食盐、紫薯、红薯叶、蛋白粉、山药、高杆白菜、花生叶、金银花、藿香、山楂、甘草、野菊花、连翘、柴胡、牛蒡子、陈皮、复合添加剂。本发明饲料组分合理科学，在满足母猪营养的同时也能加强自身免疫力，并且能够及早预防母猪红皮病。本发明猪饲料制备工艺简单高效，适合大规模推广。